Successful use of MiniMed 780G during pregnancy - Khaled Ahmed Baagar (17032266) (2023)
Background Pregnancy in the setting of type 1 diabetes (T1D) is associated with increased morbidity and mortality. There is strong evidence to suggest that the use of continuous glucose monitoring (CGM) is associated with better glycemic control and reduced adverse pregnancy outcomes. As hybrid closed-loop (HCL) systems are increasingly used among women with T1D, many prefer to continue off-label use of these systems during pregnancy. However, most of the available HCL systems’ glucose targets and algorithms are not designed to overcome the challenges that face insulin therapy during pregnancy. We are reporting on two females with T1D who used MiniMed 780G, an advanced HCL system, during their pregnancy with good outcomes. Cases presentation Case 1: A 23-year-old woman with T1D presented at 6 weeks gestation. She used MiniMed 780G before pregnancy and throughout her pregnancy. By assisting her HCL system with some techniques, such as earlier bolusing before meals and the use of fake carbs to correct high glucose, and providing frequent follow-up, she achieved pregnancy-specific HbA1C and CGM glycemic targets and had good perinatal outcomes. Case 2: A 26-year-old female with T1D presented at 10 weeks gestation. She had been using MiniMed 670G since before pregnancy, thereafter, she was shifted to MiniMed 780G at 23 weeks gestation. We offered her the same techniques to support her HCL, and she achieved pregnancy-specific time in range (psTIR) in the 3rd trimester with good perinatal outcomes. Conclusion We could achieve most of the pregnancy-specific glycemic targets with good maternal, fetal, and neonatal outcomes using MiniMed 780G, assisted with some techniques to increase the efficiency of insulin therapy during pregnancy. Other Information Published in: Journal of Clinical and Translational Endocrinology: Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jecr.2023.100156